Influence of spine biomechanics and sagittal balance on the outcome of lumbar discectomy - Carrizo, José Poblete; Martínez, Jesús; González, Julio; Mosteiro, Alejandra; Torné, Ramon; Di Somma, Alberto; Ríos, José; Enseñat, Joaquim; Fuster, Salvador (Frontiers in Surgery, 2025)
PurposeSpine biomechanics, particularly sagittal balance and spino-pelvic angulation are determinant factors in the understanding of lumbar degenerative disease. These concepts translated into objective measurements are progressively being integrated into clinical practice. The present study explores them as prognostic factors in patients undergoing lumbar microdiscectomy, which could help identify those at higher risk of surgical failure.MethodsProspective analysis of patients treated with lumbar microdiscectomy (n = 52) and healthy control subjects (n = 45) in a single tertiary centre. Follow up of 12 and 24 months after surgery, with radicular and lumbar pain evaluation according to the Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI). Comparison of several objective spinal biomechanic factors, measured by a single experienced radiologist. Assessment of spinal sagittal balance as a prognostic factor after lumbar discectomy.ResultsCompared to healthy individuals, patients with symptomatic lumbar disc herniation showed lower thoracic kyphosis (39.03 vs. 34.42° p = 0.034), lower thoraco-lumbar transition T10-L2 angulation (6.79 vs. 2.08° p = 0.005), lower lumbar lordosis (59.54 vs. 48.36° p < 0.001) and lumbo-sacral angulation L4-S1 (40.20 vs. 29.16° p < 0.001), lower pelvic incidence (54.71vs 49.86° p = 0.014) and lower sacral slope (42.07 vs. 33.34° p < 0.001). Sagittal balance (SVA) was negative in healthy subjects −3.09 mm and positive lumbar-disc patients 15.04 (p = 0.013). Noteworthy, the radicular and lumbar pain and disability outcomes 12 and 24 months after surgery were significantly better in the group with normal sagittal balance (ODI 14.52 vs. 40.06 p < 0.001; radicular VAS 2.74 vs. 5.58 p < 0.001; lumbar VAS 3.61 vs. 4.06 p < 0.001).ConclusionLumbar degenerative disc disease represents a major burden for healthcare systems; thus, its management is determinant. Lumbar discectomy shows overall positive results, with a significant reduction of pain and disability in the majority of cases. However, a subgroup of patients, still not well defined, may experience persistent pain after the intervention. The use of objective measurements of sagittal balance may help identify these patients for which simple discectomy may not suffice and contribute to treatment planification.